Caracterization from hearing thresholds from dentists in a poulation from Curitiba city / PR, Brazil - Gonçalves, Cláudia Giglio de Oliveira; Marques, Jair Mendes; Ribas, Angela; de Lacerda, Adriana Bender Moreira; Lobato, Diolen Conceição Barros; Costa, Gisele Lacerda; Gonçalves, Geyza Aparecida (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The dentists are exposed to noise in their work place, being likely to develop of hearing loss neurosensory with induced characteristics by noise.Objective: Analyze the hearing thresholds from dentists characterizing them according to gender, age and time of service.Method: The form of the study is cross-section (or sectional), prospective, that analyzed the hearing thresholds from 115 dentists, through tone audiometry of 500 Hz to 8000 Hz by airway or bone conduction. Were analyzed the tonal hearing thresholds from the group of dentists by gender, regarding the age and time of service and applied statistical procedures for the edition of data.Results: Were observed average tonal hearing thresholds with configuration from acoustic notch, being more accentuated in the male gender. There is sensorineural hearing loss in 28 (24,34%) dentists, 8 (14,54%) between female gender and 20 (33,33%) between the male gender, the proportion of subjects with altered hearing is significantly bigger in the male gender (p = 0,0208). The tonal hearing thresholds for the male gender shown to be worse than in the females when analyzed by age and time of service, but the men were older and with more time of service than the women.Conclusion: The dentists presented sensorineural hearing loss with acoustic notch (being more present in the male gender) with worsening of hearing and time of service, especially after 21 years of work.
Keywords: dentists; occupational diseases; hearing loss provoked by noise